Annual General Meeting of the Institute (The Southern African Institute of Mining and Metallurgy, 1973)
The Annual General Meeting of the Institute was held in Kelvin House, Johannesburg, on Wednesday, 22nd August, 1973. Dr J. P. Hugo (President) was in the Chair. There were also present 64 Fellows, 20 Members, 5 Associates, 3 Students, and 34 Visitors, making a total of 126. The President declared the meeting open at 4.05 p.m. OBITUARIES The President: It is my sad duty to announce the death of the following members of the Institute C. Boocock, R. J. G. Moore, M. P. Pearse, and A. I. Sussman, all Fellows, and W. T. Dalling, a Life Member. As a mark of respect to the memory of the deceased and in sympathy with the bereaved, I ask you to rise and observe a few moments' silence. MINUTES Die President: Item twee op die agenda is die bekragtiging van die notules van die jongste Algemene Vergadering van die Instituut. Daar die notules in die Augustus uitgawe van die Joernaal gepubliseer is, vra ek u toestemming dat dit as sulks bekragtig word. Toestemming verleen. WELCOME TO VISITORS The President: It is my very great pleasure to welcome all the distinguished guests who have honoured us with their presence this afternoon; in particular, a hearty word of welcome to the Honorary President of the Institute, Mr Plumbridge, the President of the Chamber of Mines. You are doubly welcome here, sir, and we thank you for your presence. Also to that old member and stalwart, the Honorary Vice-President of the Institute, Mr Tommy Gibbs, the Government Mining Engineer-you're very welcome, Mr Gibbs. Then, we are particularly privileged this afternoon to have an Honorary Member with us, the Minister of Mines for Rhodesia, Mr Dillon. You will recall that he honoured us with his company last year. Mr Dillon, we are very appreciative and hope that this is now a standing arrangement. We are also honoured by the presence of some thirteen Presidents, Vice-Presidents, or Chairmen of our sister scientific and technical organizations. I shall rapidly read their names, but they must all feel assured that they are very welcome here today. Firstly, one of our own Past Presidents and members, Mr Geoff Goode in his capacity as President of the Associated Scientific and Technical Societies of South Africa; Mr L. R. Robinson, President of the South African Institution of Mechanical Engineers, and Mrs Robinson; Mr G. Goedhals, President of the South African Institute of Electrical Engineers ; Dr Antrobus, President of the Geological Society of South Africa, and Mrs Antrobus; Mr T. V. Dean, Vice-President of the Institute of Land Surveyors of the Transvaal, and Mrs Dean; Mr R. M. Stroh, President of the Mine Ventilation Society of South Africa; Mr Ken Steele, President of the Association of Mine Managers, and Mrs Steele; Mr Mike Gericke, President of the South African Council for Professional Engineers; Mr R. G. Matthews, President of the Institute of Mine Surveyors of South Africa; Mr P. H. Pettifor, President of the Institute of Production Engineers, London, and Mrs Pettifor ; Dr Nico Stutterheim, Chairman of the South African Institute of Chemical Engineers, and Mrs Stutterheim; Professor F. A. van Duuren, Chairman of the Engineers' Liaison Committee in Pretoria; also, I haven't spotted him but I trust he is here-Mr Alex Bain, who is Chairman of this Institute's Witbank/Middelburg Branch. To one and all, ladies and gentlemen, a hearty word of welcome. Not last on our list, a word of welcome to Mr Eric Boden, the Manager of A.S. and T.S. We also have with us I trust, Dr Deist, and his good lady-Dr Deist will be figuring in our proceedings later this afternoon. Also Mr Barcza and Mrs Barcza. Mr Bareza, a former President of the Institute, also has a task to perform. Then, I hope two of our student prize winners are here-Mr Beetge and Mr Painting. Then we also have Mr Roberts, who is welcome in his capacity as co-author with Dr Deist. Then, last of all, a hearty word of welcome to Dr Helen Glen (I am not sure whether she has arrived yet, but she is certainly due to come)-the new Honorary Editor of the Institute's Journal. MEMBERSHIP The President: I have pleasure in announcing that, their names having been published in accordance with By-law 5.2.2, the following have been elected by Council to membership in the following grades Fellows: W. G. Jayes and F. K. Wright Members: D. W. Penman, A. W. Bryson, and D. L. Gibbs Graduates: R. J. Adey, J. P. Bond, R. C. Dunne, G. M. Entwhistle, J. M. Rendu, J. P. S. Turner, and A. P. van Jaarsveld Associates: A. Ellis, B. R. Hambly, A. J. Johansen, and G. W. Tregoning